2021
DOI: 10.1038/s41598-021-81589-7
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolutionary history of domestic chickens inferred from a large population study of Thai red junglefowl and indigenous chickens

Abstract: In this study, we aimed to elucidate the origin of domestic chickens and their evolutionary history over the course of their domestication. We conducted a large-scale genetic study using mitochondrial DNA D-loop sequences and 28 microsatellite DNA markers to investigate the diversity of 298 wild progenitor red junglefowl (Gallus gallus) across two subspecies (G. g. gallus and G. g. spadiceus) from 12 populations and 138 chickens from 10 chicken breeds indigenous to Thailand. Twenty-nine D-loop sequence haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 76 publications
2
78
0
2
Order By: Relevance
“…Komiyama et al (2003) [23] hypothesized that the origin of Haplogroup H (described as "Group A" in their study) was China because Haplogroup H was not found in other areas in the world when the paper was published. Since their study, Haplogroup H has been found in Southern China, Vietnam, and Thailand [10,11,19,20] (Dich et al, 2011, Direct submission to GenBank). These results were congruent with previous hypotheses regarding the northern and southern introduction routes of Japanese indigenous chickens [30,31].…”
Section: Genetic Relationships Of Japanese Indigenous Chickens With C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Komiyama et al (2003) [23] hypothesized that the origin of Haplogroup H (described as "Group A" in their study) was China because Haplogroup H was not found in other areas in the world when the paper was published. Since their study, Haplogroup H has been found in Southern China, Vietnam, and Thailand [10,11,19,20] (Dich et al, 2011, Direct submission to GenBank). These results were congruent with previous hypotheses regarding the northern and southern introduction routes of Japanese indigenous chickens [30,31].…”
Section: Genetic Relationships Of Japanese Indigenous Chickens With C...mentioning
confidence: 99%
“…Haplogroups F and G are found to be restricted to Southwestern China and Southeast Asia [11,12,18]. Haplogroup H consists of chickens in restricted regions in southwestern China, Japan, and Thailand [11,19,20], and haplogroups I and J have been reported only for a few indigenous chickens in Northeast India and Southeast Asia [11,18,20] and wild red junglefowls in Southeast Asia [11,20]. Haplogroups K and W-Z have been rarely found in wild red junglefowls in Northeast India and Southwestern China, respectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…and four breeds from Laos (0.62 to 0.69 and 0.64 to 0.68, respectively) [20] but were less than 0.60 in nine Thai indigenous chicken breeds (averaging 0.56 and 0.57, respectively) [44]. In…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%
“…This haplogroup is widely distributed in red junglefowl in Thailand [44], whereas it is comparatively rare in domestic chickens and has only been reported in a limited number of indigenous chickens in Indonesia [50] and Thailand [44]. These results thus indicate that In a number of previous studies, the genetic diversity of indigenous chickens in Southeast Asia has been investigated using microsatellite DNA markers [18,20,44,51]. For example, Cuc et al ( 2010) [18] examined the genetic diversity of nine indigenous chicken breeds in Vietnam and found that the mean number of alleles per locus (Na), observed heterozygosity (Ho), and expected heterozygosity (He) were 6.09, 0.60, and 0.63, respectively.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…However, it is equally important to understand the immune regulation system in local breeds of chicken, particularly in developing countries. Indigenous breeds of chickens stand in an intermediate position between wild and commercial breeds [ 24 ].…”
Section: Discussionmentioning
confidence: 99%